(3EOGQI efXheGJ GdJShjb GdYQHj h GdOhdj (B/s - (3GdfLGQ, aQjOs ((3GdEScfOQjI (B:s (3eDSSI THGH GdLGeYI ,s, 2005)
(3GdJShjb fXGe LRFj Gh aQYj ef GfXeI Gj eLJeY h ef Ke aGdJZjQGJ GdHjFjI aj GdeLJeY PGJ YdGbI GQJHGWjI eY GdJShjb h GdeLfeY GdOhdj h GdeMdj Gdjhe aj JWhQ OGFH eeG jMbb JZjQGJ aj GdJShjb h GOGQGJg GdG Gf QOhO GdaYd Hjf GdJShjb h GdHjFI JNJda ef OhdI dCNQi h ef hbJ dCNQ h jYcS GdJWhQ GdJShjbj aj GdeGVj GdJhbYGJ GdJShjbjI HGdeSJbHd h JQHW GdJZjQGJ GdeSJbHdjI aj GdJShjb HGdJZjQ aj MLe h JQcjH GdScGf h echfGJ GdONd Gdbhej h GdGfJGL GdeMdj h GJLGgGJ GdGSJjQGO h GdJUOjQ h GdJShjb GdOhdj h GdJZjQGJ GdafjI aj GdGfJGL h GdgLQI GdeYGcSI ddOGNd h GdNGQL h ZjQgG h jYJHQ GdeTcdI GdJShjbjI GdYQHjI eMUdI fbU caGAI GdJLGQI h GdJShjbs
Keywords: (3EOGQI GdCYeGd GdOhdjI s; (3GdJShjbs; (3dJLGQIs; (3GGdEbJUGOs